2017
DOI: 10.20944/preprints201702.0091.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Methods for Fracture Toughness Evaluation of Tool Steels with Post-Tempering Cryogenic Treatment

Abstract: Abstract:Cryogenic treatments are usually carried out immediately after quenching, but their use can be extended to post tempering in order to improve their fracture toughness. This research paper focuses on the influence of post-tempering cryogenic treatment on the microstructure and mechanical properties of tempered AISI M2, AISI D2, and X105CrCoMo18 steels. The aforementioned steels have been analysed after tempering and tempering + cryogenic treatment with scanning electron microscopy, X-ray diffraction fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In most demanding automotive, aerospace and manufacturing applications, steel often also undergoes a cryogenic treatment (CT) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] which provides a sound combination of hardness, wear resistance, toughness and deformation work [22][23][24][25][28][29][30]. Moreover, it is widely accepted that the addition of a cryogenic step to the heat treatment also leads to an overall increase in fatigue strength [18,27,31,32], although few experimental data are available on the fatigue behaviour of notched components [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In most demanding automotive, aerospace and manufacturing applications, steel often also undergoes a cryogenic treatment (CT) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] which provides a sound combination of hardness, wear resistance, toughness and deformation work [22][23][24][25][28][29][30]. Moreover, it is widely accepted that the addition of a cryogenic step to the heat treatment also leads to an overall increase in fatigue strength [18,27,31,32], although few experimental data are available on the fatigue behaviour of notched components [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…is technology has been widely studied on a broad range of materials by numerous researchers in recent years, such as various steels [8][9][10], nonferrous alloys [11,12], metallic glass [13], polymers [14], etc. Considerable research has demonstrated that cryogenic treatment can improve mechanical properties of steels, such as hardness [15], wear resistance [9,16], toughness [17,18], or relieving residual stress [19]. erefore, it has been proved to be an effective and promising technology to improve certain mechanical properties of steel.…”
Section: Introductionmentioning
confidence: 99%
“…, and other rock mechanical parameters influencing how the fracture nucleates [5], fracture size and geometry, but fracture sizes and geometry adopted in hydraulic fracture design and modelling, Discrete Fracture Network (DFN) modeling, and Finite Element Modeling (FEM); are most often overestimated. Although scratch tests are applicable nowadays to several fields of science and engineering, ranging from strength characterization of rocks and cements/ceramics [6,7,8,9,10,11,12], to damage of polymers [13,14,15,16,17,18,19,20,21] and metals [22,23,24,25], and quality control of thin films and coatings [16,19]; the underlying rock failure mechanisms, characterization, and applications has not been fully explored. Although several researchers have attempted to evaluate and quantify UCS, fracture toughness, and other rock mechanical properties in conventional and unconventional reservoir rocks using indentation and scratch testing methods, but there remain differing opinions on the fundamental approach and principles to be adopted in estimating those parameters.…”
Section: Introductionmentioning
confidence: 99%